(untitled) (Estudos em Design, 2024)
Editores Cristina Portugal Rita Couto Avaliadores desta edição v. 32, n. 1 (2024) Adriana Gralow Adriana Miranda Adriana Sampaio Leite Alexandre Oliveira Aline Savi Álvaro Sousa Ana Beatriz Pereira de Andrade Ana Berwanger Ana Pazmino André Ribeiro de Oliveira Angelica Adverse Antonio Colchete Filho Beany Monteiro Cassia Carrara Domiciano Cayley Guimaraes Cláudia Zacar Clice Mazzilli Chrystianne Ivanóski Cristiane Aun Bertoldi Cyntia Malaguti de Sousa Daniel Grizante de Andrade Daniel Raposo Daniela Estaregue Alves Debora Buonano Deborah Christo Doris Kosminsky Edson Rufino Elizabeth Romani Eloiza Corrêa da Silva Emília Duarte Eva Rolim Miranda Everton da Silva Filipe Campelo Xavier da Costa Frederico Braida Gabriel Patrocinio Gabriela Carneiro Gabriela Perry Gisela Campos Gisele Saraiva Ione Bentz Isadora Dickie Juliana Bueno Juliana Franco Karina Porto Bontempo Kando Fukushima Kátia Carvalhaes Pêgo Laura Martins Letícia Affini Luiz Agner Madalena Grimaldi Maíra Woloszyn Matheus Cezarotto Marcelo Forcato Marcio Guimarães Maria Do Carmo Gonçalves Curtis Maria Teresa Lopes Marilda Lopes Pinheiro Queluz Marina Kunst Mariano Lopes de Andrade Neto Maristela Ono Nelson Kuwahara Olavo Neto Paula Piva Linke Rafaella Peres Raimundo Diniz Ravi Passos Renata Cadena Renata Wanderley Sandra Maria Souza Sérgio Luciano da Silva Vagner Godói Vera Damazio Verônica Freire Viviane Nunes